Exploring the dimensions of community health literacy: a scoping review - Senanayake, K.I.D.F.; Kuruppu, D.C. (University of Colombo, 2023)
Community Health Literacy (HL) is a multidimensional concept that plays a pivotal role in promoting individual’s understanding, access to, and utilization of health information and services within their respective communities. A scoping review was conducted following PRISMA guidelines aiming to explore the key concepts including health information sources used, related socio-demographic factors, knowledge gaps, and interventions to improve HL. Three electronic databases (PubMed, Medline and CINAHL) were consulted using terms “health literacy, community, and the general public”. The search generated a total of 3899 articles. After removing duplicates, the publication year was limited to 2018-2023 and 1151 articles were screened through Rayyan software, 481 articles were included in the final analysis. The extracted data was analysed and synthesized using both quantitative and qualitative approaches. Majority of the research related to HL has been conducted in the European Region (n=210, 44%) followed by the Americas Region (n=160, 33%), South-East Asia Region (n=48, 10%), Western Pacific Region (n=32, 7%) and Eastern Mediterranean Region (n=31, 6%). Most of the community uses television, social media, celebrity webpages, friends, family members, and pharmaceutical companies as health information sources rather than information from healthcare specialists. Age, gender, education level, language proficiency, economic status were the identified major socio-demographic factors associated with HL. Majority of the research studies (n=331, 69%) have examined HL in a general aspect, while the remaining 36% (n=54) focused on Mental HL (n=54, 36%), COVID-19 HL (n=29, 19%) and Digital HL (n=28, 19%). HL related to prescribed medication management and decision-making in medical management were found to be significant knowledge gaps. Community-based health education programs and collaborations between healthcare providers and community organizations were identified as leading interventions to enhance community HL. The review suggests Librarians are ideally placed to raise awareness of the impact of low HL and to work with health professionals by contributing to improving the quality and accessibility of healthcare information for the public. The study recommends that addressing the identified knowledge gaps is essential to provide equitable healthcare outcomes, reduce healthcare costs, and improve overall well-being for individuals and communities.
Keywords: community health; general public; health literacy